Sealed computation: Abstract requirements for mechanisms to support trustworthy cloud computing - Abdullah, Lamya; Freiling, Felix; Quintero, Juan; Benenson, Zinaida (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2019)
In cloud computing, data processing is delegated to a remote party for efficiency and flexibility reasons. A practical user requirement usually is that the confidentiality and integrity of data processing needs to be protected. In the common scenarios of cloud computing today, this can only be achieved by assuming that the remote party does not in any form act maliciously. In this paper, we propose an approach that avoids having to trust a single entity. Our approach is based on two concepts: (1) the technical abstraction of sealed computation, i.e., a technical mechanism to confine the processing of data within a tamper-proof hardware container, and (2) the additional role of an auditing party that itself cannot add functionality to the system but is able to check whether the system (including the mechanism for sealed computation) works as expected. We discuss the abstract technical and procedural requirements of these concepts and explain how they can be applied in practice.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Auditor; Cloud computing; Cloud service; Security requirements; Trusted computing; Trustworthy computing

Sealed computation: a mechanism to support privacy-aware trustworthy cloud service - Abdullah, Lamya; Quintero, Juan (Information and Computer Security, 2019)
Purpose: The purpose of this study is to propose an approach to avoid having to trust a single entity in cloud-based applications. In cloud computing, data processing is delegated to a remote party for efficiency and flexibility reasons. A practical user requirement usually is data privacy; hence, the confidentiality and integrity of data processing needs to be protected. In the common scenarios of cloud computing today, this can only be achieved by assuming that the remote party does not in any form act maliciously. Design/methodology/approach: An approach that avoids having to trust a single entity is proposed. This approach is based on two concepts: the technical abstraction of sealed computation, i.e. a technical mechanism to confine a privacy-aware processing of data within a tamper-proof hardware container, and the role of an auditing party that itself cannot add functionality to the system but is able to check whether the system (including the mechanism for sealed computation) works as expected. Findings: Discussion and analysis of the abstract, technical and procedural requirements of these concepts and how they can be applied in practice are explained. Originality/value: A preliminary version of this paper was published in the proceedings of the second International Workshop on SECurity and Privacy Requirements Engineering (SECPRE, 2018).
CRIS-Team Scopus Importer:2019-07-02
Keywords: Auditor; Cloud service; Data privacy; Privacy by design; Sealed computation; Trustworthy cloud requirements

User Acceptance Factors of Usage-Based Insurance - Quintero, Juan; Karaseva, Victoria; Gassmann, Freya; Benenson, Zinaida (Advances in Transdisciplinary Engineering, 2023)
Intelligent Transportation Systems (ITS) are utilized in car insurance policies known as Usage-Based Insurance (UBI), where driving data is collected using a telematics device to determine driving behavior. This enables offering personalized car insurance fees based on driving performance. Current research focuses on advantages, disadvantages, and privacy aspects of UBI, paying less attention to its user acceptance. In this work, we propose a UBI acceptance model based on an adaptation of the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) and test it with 585 participants by means of structural equation modeling. We find that social influence and hedonic motivation are the most important predictors of the intention to use UBI, and perceived privacy influences it indirectly. Furthermore, we refine the model with new connections, improving model fit.
CRIS-Team Scopus Importer:2023-09-22
Keywords: technology acceptance; telematics insurance; Usage-Based insurance

Users' Privacy Concerns and Attitudes towards Usage-based Insurance: An Empirical Approach - Quintero, Juan; Railean, Alexandr (VEHITS: PROCEEDINGS OF THE 8TH INTERNATIONAL CONFERENCE ON VEHICLE TECHNOLOGY AND INTELLIGENT TRANSPORT SYSTEMS, 2022)
CRIS-Team WoS Importer:2022-07-15